Peningkatan Kompetensi Marketing Officer melalui Pelatihan Digital Marketing dan Strategi Komunikasi Pemasaran - Luthfi Luthfi; Mahyu Danil; Laina Fadhliah; Rahmad Hidayat; Muhammad Muhammad (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Digital transformation requires Management students—as aspiring professionals—to possess marketing competencies that are not merely conceptual but also practical. A key area for strengthening is the ability to perform the role of a marketing officer, specifically through mastering digital marketing and marketing communication strategies. This community service initiative aims to enhance students' knowledge and skills in strategically leveraging digital technology for marketing activities. The program was conducted with a student community across four stages: preparation, training delivery, hands-on practice and mentoring, and evaluation. The curriculum covered the role and competencies of a marketing officer, digital marketing concepts, consumer segmentation and targeting, social media management, branding, content development, copywriting, and marketing communication strategies. The program employed various methods, including interactive lectures, discussions, demonstrations, case studies, practical exercises, and mentoring. The results indicate an improved understanding among participants regarding the marketing officer role and the use of digital media as a marketing tool. Participants also gained skills in identifying target consumers, selecting digital media, crafting promotional messages, developing content, and designing marketing communications tailored to consumer characteristics. This initiative provided practical experience that supports student readiness to perform marketing officer functions, develop entrepreneurial activities, and meet the demands of an increasingly digitalized workforce.